Preparation method of biomass composite material with polyvinyl alcohol as formaldehyde-free adhesive
Patent Information
- Application Number
- CN202510397124.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2026-10-16
AI Technical Summary
[0009]本发明的目的是为了解决现有甲醛胶黏剂存在游离甲醛释放,且现有生物质复合材料因使用热压工艺导致孔隙无序,进而提出一种以聚乙烯醇为无醛胶黏剂的生物质复合材料制备方法
[0016] 1. The polyvinyl alcohol adhesive of this invention uses only polyvinyl alcohol as its raw material. The raw material is non-toxic, and the solvent is water. It is green and environmentally friendly, with no formaldehyde added. It can fundamentally solve the indoor formaldehyde pollution hazards that people have long faced, and avoid the use and emission of large amounts of organic solvents. Considering the entire production process, this adhesive is non-toxic and harmless to consumers, industrial producers and the environment. It is a truly healthy and environmentally friendly adhesive.
Smart Images

Figure CN122913490A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of wood material deep processing / adhesive technology.
[0002] This invention belongs to the field of biomass composite material preparation, and specifically relates to a method for preparing high-strength formaldehyde-free biomass composite materials by cryogenic casting using biomass materials as raw materials and polyvinyl alcohol as adhesive. Background Technology
[0003] The production of biomass composites requires the extensive use of adhesives. To achieve better bonding performance and reduce costs, formaldehyde-based thermosetting adhesives, such as urea-formaldehyde resin (UF), phenolic resin (PF), and resorcinol-formaldehyde (RF), are commonly used. However, these formaldehyde-based adhesives are considered priority pollutants due to their formaldehyde emissions. Furthermore, formaldehyde is irritating to skin and mucous membranes, and its release into the environment poses a potential health threat to consumers and workers in manufacturing facilities; therefore, it is classified as a carcinogen that may cause nasopharyngeal carcinoma in humans. To reduce the emission of formaldehyde and volatile organic compounds from wood products, researchers have developed various sustainable, formaldehyde-free alternative adhesives, such as soybean-based formaldehyde-free adhesives, polyisocyanate formaldehyde-free adhesives, and polyvinyl alcohol formaldehyde-free adhesives. However, soybean protein formaldehyde-free adhesives have high development costs and poor anti-mildew and antibacterial properties, while polyisocyanate formaldehyde-free adhesives are highly sensitive to humidity and temperature and can cause secondary pollution.
[0004] Polyvinyl alcohol (PVA) is one of the few and most widely produced water-soluble polymers in the world, with an annual output of up to 12 billion kilograms. With abundant raw materials, it is a sustainable and environmentally friendly material. Furthermore, PVA possesses advantages such as strong adhesion, chemical stability, and biodegradability, making it suitable for preparing water-based environmentally friendly adhesives.
[0005] Cryo casting is a wet processing technique that utilizes the directional freezing of an aqueous (or other solvent) suspension (ceramics, metals, or polymers) to directly self-assemble particles, forming highly porous bulk materials. This technique is highly flexible and inexpensive. Since Sylvain Deville proposed cryo casting, researchers have used it in the preparation of ceramics and engineered wood products. Researchers have also found that polyvinyl alcohol exhibits excellent properties during cryo casting, as exemplified by the polyvinyl alcohol-gelatin-Fe composite material manufactured by Maimaitiyiming et al. using cryo casting. 3+ The hydrogel exhibits remarkable strength, reaching 2.5 MPa.
[0006] Chinese patent application number CN 112969523A, entitled "Cryogenic Casting Ceramic Membrane for Size-Based Filtration", discloses a method for manufacturing cryogenic casting materials with internal structures, but it only applies the cryogenic casting method to the field of ceramic materials and does not involve biomass composite materials.
[0007] Chinese patent application number CN 113861895A, entitled "A formaldehyde-free adhesive and its manufacturing process for fiberboard for milling door panels", discloses a manufacturing process for using a formaldehyde-free adhesive in fiberboard for milling door panels. However, this process results in disordered pores in the hot-pressed wood board, which limits its application in fields such as heat insulation and sound absorption.
[0008] If a biomass composite material can be developed that uses only polyvinyl alcohol as an adhesive, employs a manufacturing process that can resolve the contradiction between porosity and strength, and is low-cost and easy to operate, then its environmental significance and economic value will be enormous. Summary of the Invention
[0009] The purpose of this invention is to address the problems of free formaldehyde release in existing formaldehyde adhesives and disordered pores in existing biomass composite materials due to the use of hot pressing processes. Therefore, this invention proposes a method for preparing biomass composite materials using polyvinyl alcohol as a formaldehyde-free adhesive.
[0010] The present invention provides a method for preparing biomass composite materials using polyvinyl alcohol as a formaldehyde-free adhesive, which is carried out according to the following steps:
[0011] (1) Dissolve polyvinyl alcohol (PVA) particles in water at 70-80°C and stir for 1-3 hours to form a PVA solution with a mass fraction of 8%-12%.
[0012] (2) Mix biomass materials and PVA adhesive at a mass ratio of (5-15):100, remove bubbles under vacuum, and then inject into a mold composed of thermally conductive and thermally insulating materials.
[0013] (3) Apply the freezing medium along the longitudinal direction of the mold to form a directional temperature gradient and freeze for 20-40 minutes;
[0014] (4) Gradient heating and drying, repeating the freeze-drying step 2 to 5 times to obtain a biomass composite material with directional pore structure.
[0015] The beneficial effects of this invention are:
[0016] 1. The polyvinyl alcohol adhesive of this invention uses only polyvinyl alcohol as its raw material. The raw material is non-toxic, and the solvent is water. It is green and environmentally friendly, with no formaldehyde added. It can fundamentally solve the indoor formaldehyde pollution hazards that people have long faced, and avoid the use and emission of large amounts of organic solvents. Considering the entire production process, this adhesive is non-toxic and harmless to consumers, industrial producers and the environment. It is a truly healthy and environmentally friendly adhesive.
[0017] 2. The polyvinyl alcohol adhesive of this invention is the simplest wood adhesive to date. It can be dissolved simply by heating, has no technical barriers, requires very simple equipment, has mild reaction conditions, and is easy to industrialize.
[0018] 3. No curing agent needs to be added during the production of biomass composite materials from polyvinyl alcohol according to the present invention, and the curing conditions are simple.
[0019] 4. This invention utilizes advanced cryogenic casting technology. Compared to traditional hot pressing, cryogenic casting can produce a highly oriented pore structure. During the freezing process, ice crystals grow in a specific direction, leaving pores aligned along the ice crystal growth direction. This oriented pore structure is crucial for many applications.
[0020] 5. The cryogenic casting technology used in this invention typically does not require the use of large amounts of organic solvents or toxic chemical reagents, which can reduce potential harm to human health and the environment, and is in line with the new green development concept.
[0021] 6. The finished biomass composite material shows that its various properties fully meet the requirements of the latest national standard (GB / T 17657-2022) for indoor board materials, and its comprehensive performance is comparable to that of existing urea-formaldehyde resin adhesives. The polyvinyl alcohol adhesive has a low bonding cost, with the adhesive costing only about 1,500 yuan / ton, which is lower than the cheapest urea-formaldehyde adhesive on the market (≥1,800 yuan / ton). Attached Figure Description
[0022] Figure 1 The image shows the biomass composite material obtained in Example 1 (photographed from a frontal view, magnified 2.1X).
[0023] Figure 2 The infrared spectrum of the PVA solution used in Example 1 and the resulting biomass composite material is shown below.
[0024] Figure 3 The mold made of copper sheet and polytetrafluoroethylene in Example 1
[0025] Figure 4 This is a scanning electron microscope image of the surface of the biomass material used in step one of Example 1.
[0026] Figure 5 This is a scanning electron microscope image of the cross-section of the biomass composite material obtained in step two of Example 1.
[0027] Figure 6 The graph shows the compressive strength data of the biomass composite material obtained in Example 1 before and after immersion in water.
[0028] Figure 7The graph shows the elastic modulus data of the biomass composite material obtained in Example 1 before and after immersion in water.
[0029] Figure 8 The water absorption rates of the biomass composite material obtained in Example 1 at 2h and 24h are shown.
[0030] Figure 9 The thickness expansion rate of the biomass composite material obtained in Example 1 at 2h and 24h.
[0031] Figure 10 The graph shows the compressive strength data of the biomass composite material obtained in Example 2 before and after immersion in water.
[0032] Figure 11 The graph shows the elastic modulus data of the biomass composite material obtained in Example 2 before and after immersion in water.
[0033] Figure 12 The porosity-compressive strength relationship diagram of the biomass composite material obtained in Example 1 is shown. Detailed Implementation
[0034] Specific Implementation Method 1: This implementation method describes a method for preparing biomass composite materials using polyvinyl alcohol as a formaldehyde-free adhesive, which is carried out according to the following steps:
[0035] (1) Dissolve polyvinyl alcohol (PVA) particles in water at 70-80°C and stir for 1-3 hours to form a PVA solution with a mass fraction of 8%-12%.
[0036] (2) Mix biomass materials and PVA adhesive at a mass ratio of (5-15):100, remove bubbles under vacuum, and then inject into a mold composed of thermally conductive and thermally insulating materials.
[0037] (3) Apply the freezing medium along the longitudinal direction of the mold to form a directional temperature gradient and freeze for 20-40 minutes;
[0038] (4) Gradient heating and drying, repeating the freeze-drying step 2 to 5 times to obtain a biomass composite material with directional pore structure.
[0039] In this embodiment, step one, stirring at 200-500 rpm for 12 hours, is to ensure that the polyvinyl alcohol (PVA) completely penetrates the biomass material and forms a strong adhesive network. Placing the mixture in a vacuum chamber removes air bubbles from the PVA-biomass material mixture, resulting in a dense internal structure in the final particleboard. The molds use both thermally conductive and insulating materials because the significant difference in thermal conductivity between the two materials allows for directional freezing, resulting in a directionally arranged pore structure in the final biomass composite material.
[0040] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the molecular weight of the polyvinyl alcohol mentioned in step one is 150,000 to 250,000, and the degree of alcoholysis of the polyvinyl alcohol is 85% to 99%. Everything else is the same as in Specific Implementation Method One.
[0041] Specific Implementation Method 3: This implementation method differs from Specific Implementation Method 1 or 2 in that the biomass material mentioned in step 2 is at least one of wood flour, bamboo flour, straw, and corn cob, with a particle size of 0.1–1 mm. Other steps and parameters are the same as in Specific Implementation Method 1 or 2.
[0042] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that the mass ratio of biomass material in step two is 8% to 14%. Other steps and parameters are the same as in Specific Implementation Methods One to Three.
[0043] Specific Implementation Method 5: This implementation method differs from Specific Implementation Methods 1 to 4 in that the pressure of vacuum degassing in step 2 is -0.08MPa to -0.1MPa, and the degassing time is 10 to 14 hours. Other steps and parameters are the same as those in Specific Implementation Methods 1 to 4.
[0044] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that the temperature of the oven in step two is 50℃~100℃, and the standing time is 10h~14h. Other steps and parameters are the same as those in Specific Implementation Methods One to Five.
[0045] Specific Implementation Scheme Seven: This implementation scheme differs from Specific Implementation Schemes One to Six in that the freezing rate in Step Two and Step Three is 2-5℃ / min, and the angle between the freezing direction and the longitudinal direction of the mold is ≤15°. Other steps and parameters are the same as those in Specific Implementation Schemes One to Six.
[0046] Specific Implementation Scheme 8: This implementation scheme differs from Specific Implementation Schemes 1 to 7 in that the porosity of the biomass composite material is 40% to 60%, and the pore length-to-diameter ratio is 5:1 to 20:1. Other steps and parameters are the same as those in Specific Implementation Schemes 1 to 6.
[0047] Specific Implementation Scheme Nine: This implementation scheme differs from Specific Implementation Schemes One to Eight in that the biomass composite material prepared by the method has formaldehyde release that is undetectable (GB / T 17657-2022) and compressive strength ≥20MPa. Other steps and parameters are the same as those in Specific Implementation Schemes One to Six.
[0048] The performance indicators of this biomass composite material were measured as follows:
[0049] The physical and mechanical properties of biomass composite materials were tested after the panels were placed in a climate chamber at 20±2℃ and 65±3% relative humidity.
[0050] Thickness expansion: The test was conducted according to GB / T 17657—2022. The prepared dimensions were 35×35×35mm. 3 A biomass composite material sample with dimensions (thickness × width × length) was tested, and the thickness at the center of the sample was measured in micrometers. The sample was immersed in distilled water at 20°C to a depth of 30 mm for 2 and 24 hours. After the immersion period, the thickness was measured, and the formula for calculating the thickness expansion was:
[0051]
[0052] In the formula, TS is the thickness expansion, and T0, T2, and T are the thickness expansion coefficients. 24 The thicknesses of the samples are shown before immersion, and after immersion in water for 2 and 24 hours, respectively. These values are the average of 25 tests.
[0053] 24-hour water absorption rate: These samples were soaked. The water absorption rate increased with increasing soaking time until it stabilized. According to the procedure in GB / T 17657—2022, the water absorption A of the sample was calculated as a percentage. The formula for calculating the water absorption is as follows:
[0054]
[0055] In the formula, M1 and M2 represent the mass of the sample before immersion and after immersion in water for 24 hours, respectively. These values are shown as the average of 25 tests.
[0056] Static bending three-point bending test: conducted according to GB / T 17657—2022. Sample size: 10×50×200mm. 3 The rupture modulus MOR and apparent elastic modulus MOE, determined based on the load data (thickness, width, length), are as follows:
[0057]
[0058] Where L is the specimen width in mm; h is the specimen thickness in mm; b is the span length in mm; ΔP is the load at the proportional limit; Pmaximum is the maximum load at static bending in N; and Δf is the center deflection at the proportional limit load in mm. These values are shown as the average of ten tests.
[0059] Compressive strength test: conducted according to GB / T 17657—2022. The compressive strength σ of the specimen is calculated according to the following formula:
[0060]
[0061] Where: σ c F represents the compressive strength of the specimen along the grain, in MPa. max t is the maximum load N at which the specimen fails; b is the specimen width in mm; t is the specimen thickness in mm.
[0062] Example 1:
[0063] (1) Dissolve polyvinyl alcohol (PVA) particles in water at 70-80°C and stir for 1-3 hours to form a PVA solution with a mass fraction of 8%-12%.
[0064] (2) Divide the biomass material (particle size 0.1-1mm) into four parts according to its mass, and mix them with PVA adhesive at a mass ratio of (5-15):100. After vacuum degassing, inject the mixture into a mold composed of thermally conductive and thermally insulating materials.
[0065] (3) Apply the freezing medium along the longitudinal direction of the mold to form a directional temperature gradient and freeze for 20-40 minutes;
[0066] (4) Gradient heating and drying, repeating the freeze-drying step 2 to 5 times to obtain a biomass composite material with directional pore structure.
[0067] In this implementation Figure 5 SEM images of wood after PVA impregnation, for comparison Figure 4 It can be seen that most of the pores of the wood are blocked. This is because the wood has been soaked in PVA solution for a long time, causing PVA to enter the pores of the wood. Figure 6 , Figure 7 The graphs show the compressive strength and elastic modulus data of biomass materials before and after immersion in water at different mass fractions. This demonstrates that in biomass composite materials, the compressive strength and elastic modulus increase with increasing biomass mass. Furthermore, the addition of a third and fourth component of biomass material significantly improves the compressive strength and elastic modulus compared to the requirements of the national standard GB / T17657-2022, meeting the mechanical properties required for engineered wood products. Figure 8 and Figure 9 The water absorption rate and thickness swelling rate of biomass materials with different mass fractions were measured at 2h and 24h. It was found that the first biomass composite material exhibited the highest water absorption rate and thickness swelling rate. Furthermore, as the mass fraction increased, the water absorption rate and thickness swelling rate of the wood gradually decreased. This is likely because increasing the wood flour mass fraction helps improve the overall density of the wood block. Higher density means a more compact molecular arrangement within the wood block. This tightly packed molecular structure makes it more difficult for water molecules to penetrate the wood block. Water molecules need to overcome greater resistance to enter the wood block, thus reducing the water absorption rate.
[0068] Table 1 compares the thermal conductivity of the present invention with that of traditional particleboard.
[0069]
[0070]
[0071] It was found that the directional porous structure formed by the freeze casting process can reduce the thermal conductivity of the composite material to 0.032 W / (m·K), which is better than that of traditional particleboard (0.08 W / (m·K).
[0072] Example 2:
[0073] (1) Dissolve polyvinyl alcohol (PVA) particles in water at 70-80°C and stir for 1-3 hours to form a PVA solution with a mass fraction of 8%-12%.
[0074] (2) Take one part each of wood powder, bamboo powder, straw and corn cob with a mass fraction of 12% and a particle size of 0.1-1mm, and mix them with PVA adhesive liquid at a mass ratio of (5-15):100. After vacuum degassing, inject the mixture into a mold composed of thermally conductive material and thermally insulating material.
[0075] (3) Apply the freezing medium along the longitudinal direction of the mold to form a directional temperature gradient and freeze for 20-40 minutes;
[0076] (4) Gradient heating and drying, repeating the freeze-drying step 2 to 5 times to obtain a biomass composite material with directional pore structure.
[0077] Figure 10 , Figure 11 The figures show the compressive strength and elastic modulus data of biomass composites made from different raw materials before and after immersion in water. The results show that the mechanical properties of the prepared biomass composites all meet the requirements of the national standard GB / T17657—2022. This indicates that the method is widely applicable, and various non-grain crops can be used as raw materials, facilitating its promotion.
[0078] Table 2 shows the compressive strength tests of biomass composite materials prepared using polyvinyl alcohol formaldehyde-free adhesives in Examples 1 to 4.
[0079]
[0080]
[0081] Biomass composite materials with different mass fractions prepared using polyvinyl alcohol formaldehyde-free adhesive, as well as wood flour composite materials, bamboo flour composite materials, straw composite materials, and corn cob composite materials, exhibit compressive strength far exceeding national standards, indicating that polyvinyl alcohol formaldehyde-free adhesive has high-performance bonding strength.
[0082] Table 3. Cost Comparison of Polyvinyl Alcohol Solvent-Free Adhesive with Existing Commercial Adhesives in Example 2
[0083]
[0084] In terms of unit application cost, polyvinyl alcohol formaldehyde-free adhesive (0.62 yuan / m3) is comparable to urea-formaldehyde resin (0.74 yuan / m3), and far lower than isocyanate adhesive (3.60 yuan / m3) and soybean adhesive (1.40 yuan / m3), giving it a very good cost advantage and making it easier to promote in the market.
[0085] Example 3:
[0086] (1) Dissolve polyvinyl alcohol (PVA) particles in water at 70-80°C and stir for 1-3 hours to form a PVA solution with a mass fraction of 8%-12%.
[0087] (2) Mix biomass materials and PVA adhesive at a mass ratio of (5-15):100, remove bubbles under vacuum, and then inject into a mold composed of thermally conductive and thermally insulating materials.
[0088] (3) Apply the freezing medium along the longitudinal direction of the mold to form a directional temperature gradient and freeze for 20-40 minutes;
[0089] (4) Gradient heating and drying, repeating the freeze-drying step 2 to 5 times to obtain a biomass composite material with directional pore structure.
[0090] Table 4. Comparison of the biomass composite material of this patent with mainstream urea-formaldehyde resin (UF) hot press plates in Example 3.
[0091] index This invention (12% biomass material) UF hot press plate Formaldehyde release Not detected 0.15 mg / L compressive strength 27.34±0.21MPa 26.76±0.45MPa Thickness expansion rate (24h) ≤4% ≥8% elastic modulus ≥2640MPa ≤2580MPa
[0092] Through intuitive data comparison, the various indicators of this invention are superior to those of mainstream urea-formaldehyde resin adhesive (UF) hot press boards on the market, demonstrating excellent performance advantages and facilitating its widespread promotion in the home building materials market.
Claims
1. A method for preparing biomass composite materials using polyvinyl alcohol as a formaldehyde-free adhesive, characterized in that... Follow these steps: (1) Dissolve polyvinyl alcohol (PVA) particles in water at 70-80°C and stir for 1-3 hours to form a PVA solution with a mass fraction of 8%-12%. (2) Mix biomass materials and PVA adhesive at a mass ratio of (5-15):100, remove bubbles under vacuum, and then inject into a mold composed of thermally conductive and thermally insulating materials. (3) Apply the freezing medium along the longitudinal direction of the mold to form a directional temperature gradient and freeze for 20-40 minutes; (4) Gradient heating and drying, repeating the freeze-drying step 2 to 5 times to obtain a biomass composite material with directional pore structure.
2. The preparation method according to claim 1, characterized in that... The polyvinyl alcohol mentioned in step one has a molecular weight of 150,000 to 250,000 and a degree of alcoholysis of 85% to 99%.
3. The preparation method according to claim 1, characterized in that... The biomass material mentioned in step two is at least one of wood flour, bamboo flour, straw, and corn cob, with a particle size of 0.1 to 1 mm.
4. The preparation method according to claim 1, characterized in that... The biomass material mentioned in step two has a mass ratio of 8% to 14%.
5. The preparation method according to claim 1, characterized in that... The vacuum degassing pressure in step two is -0.08 MPa to -0.1 MPa, and the degassing time is 10 to 14 hours.
6. The preparation method according to claim 1, characterized in that... In step two, the oven temperature is 50°C to 100°C, and the settling time is 10 to 14 hours.
7. The preparation method according to claim 1, characterized in that... In step three, the freezing rate is 2–5°C / min, and the angle between the freezing direction and the longitudinal direction of the mold is ≤15°.
8. The preparation method according to claim 1, characterized in that... The porosity of the biomass composite material is 40% to 60%, and the aspect ratio of the pores is 5:1 to 20:
1.
9. The biomass composite material prepared according to the method of claim 1 has a formaldehyde release of not detected (GB / T17657-2022) and a compressive strength ≥20MPa.
Citation Information
Patent Citations
Freeze-cast ceramic membrane for size based filtration
CN112969523A
Formaldehyde-free adhesive, and manufacturing process for applying formaldehyde-free adhesive to fiberboard for routing door panel
CN113861895A